Open me up - Laura Buller; Buller, Laura (London : Dorling Kindersley, 2009)
Provides everything you need to know about the human body--from human cells and senses to brain structure and body systems. Take a trip through the history of medicine and body science from Hippocrates to the Human Genome Project. Find out more about left-handedness, memory tricks and what sensory skills are needed to be a professional food taster!
Being human. The human race ; In touch ; Living anywhere ; Ancient wisdom ; Art inside out ; Measure me up ; Looking inside ; Nowhere to hide -- Outside in. Skin ; Body decoration ; Hairy bodies ; Nail know-how ; Fingerprint files ; Skin shades ; Organ exhibition ; Spare parts ; Body builders ; Super cells ; Inside a cell ; Discovering DNA ; DNA ; Cell division ; Genetic ID -- Moving framework. Skeleton gallery ; Break a leg ; The "x" man ; Joints ; Muscle gym ; Spaced out ; Can your face speak without words? ; Fitness first! ; In hand ; On the move ; Replacement parts -- In control. Nervous network ; A tale of two brains ; Working parts ; Left or right? ; The ANS team ; Reflex actions ; Making memories ; Do not disturb! ; Fears and phobias ; Hormone diary ; Run or stay? ; Talking heads ; Body language ; Trick or cheat? ; Touch test center ; The tasty diner menu ; The taste of success ; iEye ; Your eyes in motion ; Art of illusion ; Music to our ears ; Balancing act -- Fueling your body. Food fest ; Dental kit ; Food, glorious food! ; Lemonaid ; Body fuel ; Gastric experiments ; Toilet truths ; The liver ; Staying cool, staying warm ; The hootervator ; Breathing ; Body tour ; Breathtaking -- Maintenance and transportation. Tube network ; A bloody rebellion ; Heart ; Resume : red blood cell ; Peaks and pulses ; Drain and destroy ; Blood soldiers ; Sailing through life ; Slice of life ; Heart-to-heart ; Making a splash ; Special brew -- Malfunctions and medicine. Pathogen parade ; Spreading disease ; Malaria ; Enemy within ; Human zoo ; Ancient remedies ; Vaccinate and protect ; HIV ; Case: Disease detectives ; Pandemic ; Miracle mold ; First aid ; Alternative therapies ; Making a diagnosis ; Nursing ; Under the knife ; Through the keyhole ; Medical timeline -- Life story. Puberty ; Being female ; Being male ; Mission: Conception ; Nine months ; Baby talk ; Different features ; Twins ; Lifetime ; The end ; Body preservation ; Body parts ; The next step -- Body systems database.
Includes index.
Keywords: Human body -- Juvenile literature; Human anatomy -- Juvenile literature; Human physiology -- Juvenile literature; Human body; Human anatomy; Human physiology; Literature